Improving Elementary Students' English Learning Through Think-Pair-Share Model - Ridawati Sirait (SOSCIED, 2023)
This action research aims to explore the effectiveness of implementing the Think-Pair-Share (TPS) model to improve elementary students' English learning, which consists of two cycles. Each cycle consists of the stages of planning, implementing, acting, observing, evaluating, and reflecting. The subjects of this research were 20 class V students in one of elementary schools in Deli Serdang. The object of research is an increase in learning outcomes, which include knowledge and skill competencies. The Students took multiple-choice tests to assess knowledge learning outcomes and speaking skills tests to assess skill learning outcomes at the conclusion of each cycle in order to evaluate their progress in learning English. The results demonstrate the impact of TPS on students' language proficiency, confidence in speaking, engagement, and collaboration skills. The findings provide useful insights for educators seeking innovative instructional approaches to foster effective English language learning at the elementary school level.